Paragraph Writing Barriers: A Study on The Fifth-Semester of English Department Students - Silfi Angraini; Eki Saputra (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
Writing paragraphs in English is a fundamental academic skill, yet many students still encounter various difficulties, particularly in the digital era where technology influences writing practices. This study aimed to identify the barriers faced by fifth-semester students in paragraph writing and examine the factors influencing their writing, including the role of digital technology. This research employed a descriptive qualitative design. The participants were fifth-semester students of the English Education Department at Universitas Muhammadiyah Bengkulu. The data were collected through questionnaires and interviews. The findings revealed that students experienced linguistic, cognitive, technical, and technological barriers. Linguistic barriers were the most dominant, particularly in vocabulary, grammar, and spelling. Other difficulties included cohesion, mechanics, organization, and coherence. In addition, digital technology acted as both a supporting and influencing factor. While digital tools helped students correct errors and generate ideas, excessive reliance on these tools reduced students’ confidence and independent writing ability. In conclusion, vocabulary and grammar limitations remain the primary barriers, and digital technology significantly influences students’ paragraph writing both positively and negatively. Keywords: paragraph writing, writing barriers, digital writing, linguistic barriers, writing factors.